Chemical Examination of the Fruits of Diospyros peregrina Gurke - Sampurna, T.; Siva Sankara Rao, T. (Asian Journal of Chemistry, 2010)
The brownish-yellow oil obtained from the petroleum ether extract of the fruits of Diospyros peregrina was found to be a glyceride of myristic, palmitic, stearic, oleic, linoleic and palmitoleic acids. The glycoside from the alcoholic extract was characterized as β-sitosterol-D-glucoside. The free sugars isolated were found to be fructose, galactose, glucose, lactose, mannose and sucrose. The pectin precipitated from the water extract on hydrolysis revealed the presence of arabinose, galactose and galacturonic acid in it. The protein from the defatted fruits on hydrolysis gave histidine, lysine, glycine, aspartic acid, glutamic acid, alanine, proline, methionine, leucine and tryptophan.